Grammatical Errors in the Expository Texts of Eleventh Grade EFL Students at MA Al-Asy’ari Diwek Jombang - Ni'amah, Afi (Jurnal Bina Ilmu Cendekia, 2025)
The complexity of English grammar poses significant challenges for language learners, leading to various errors. This study employed a qualitative approach to investigate the categories of grammatical errors made by 138 students and the cause of error. The study gathered qualitative data through questionnaires and tasks completed by students. The findings revealed five key areas where students struggled with grammatical errors: noun phrases, verb phrases, word order, transformation, and verb and verb construction. These errors stemmed from various factors, including interference (25.80%), overgeneralization (87.09%), performance errors (96.77%), transitional competence markers (80.64%), communication strategies (64.51%), and teacher-induced errors (67.75%). Notably, performance errors had the most significant impact. However, additional research is necessary to explore learners' psychology in English classes to enhance teaching effectiveness. This research makes a significant contribution to the field of applied linguistics, particularly in understanding grammatical errors made by foreign language learners. The contribution reinforces the notion that error analysis is not only essential for evaluating learner progress but also serves as a diagnostic tool to improve teaching methods and develop more effective and accurate instructional materials.